Local determinants of an emerging electoral hegemony: the case of Justice and Development Party (AKP) in Turkey. Issue 7 (9th November 2016) - Cinar, Kursat
ABSTRACT: "Party hegemony" is a macro-level characteristic of party systems, which is a product of persistent and overwhelming electoral victories that leads to domination of the parliamentary system by a single party. Party hegemony can only emerge through a collection of individual-level (albeit aggregated), lower-level structural, and macro-level institutional factors. This article intends to shed light on hegemonic party systems by incorporating all of these aspects. It analyses the case of the Justice and Development Party (AKP) in Turkey as a hegemonic party in the making. Based on individual-level survey data as well as an original province-level dataset, the article examines the role of ideology, pork barrel politics, economic voting, demographics, and political institutions in AKP's rising hegemony. The replicable nature of the dataset enables further testing of these findings in comparable cases for generalizability.